Geometrically Distributed 1D Photonic Crystals for Light-Reflection in All Angles - R. Jomtarak; C. Teeka; P.P. Yupapin (My University, 2012)
In this paper, we presented the general formulation of light reflection using a series of 1D PCs with different periods, made of non-absorptive materials of any refractive indices. In order to have a large bandgap – the spectral range of reflection, the periods of 1D PCs must be distributed in a geometrical progression with a common ratio, r, smaller than a maximum value of rc. The paper have presented exact expressions for rc, bandgap to mid gap ratio of the PC hetero-structure, and the minimum number of PCs to achieve the desired range of bandgap in single and all angles of incidence. The proposed method can be used to design filters for vast range of applications such as UV filters (i.e., sunglasses, eye safety glasses, UV photography filters) and visible light filters.
Keywords: Reflection; Light reflection; Photonic Crystals and Applications